Oorsprong van die drievoudige struktuur van die Heidelbergse Kategismus - Dreyer, Wim (HTS teologiese studies, 2016)
The Heidelberg Catechism was one of many catechisms that originated during the 16th-centuryReformation. It is also known that the authors of the Heidelberg Catechism made use of existingcatechisms. The content of 16th-century catechisms consisted mainly of the Decalogue, theApostolicum and the Lord’s Prayer. The Heidelberg Catechism starts with the famousintroduction, dealing with man’s only comfort, and in three sections with knowledge of our sinand misery, knowledge of our deliverance, and knowledge of how we should be grateful forour deliverance. This contribution points out that the threefold structure of the HeidelbergCatechism is not unique, but appeared in different ways in different catechisms of prominent16th-century reformers. It is also argued that the Heidelberg Catechism should be read againstLutheran and Calvinistic backgrounds. Finally, it is shown that the Heidelberg Catechismarticulated the basic Christian faith in such a beautiful and poignant manner that it stood thetest of time as a catechism and confession.